2016
DOI: 10.1097/ajp.0000000000000348
|View full text |Cite
|
Sign up to set email alerts
|

Trunk Muscle Training Augmented With Neuromuscular Electrical Stimulation Appears to Improve Function in Older Adults With Chronic Low Back Pain

Abstract: Objectives To assess the feasibility of a trial to evaluate a trunk muscle training program augmented with neuromuscular electrical stimulation (TMT+NMES) for the rehabilitation of older adults with chronic LBP and to preliminarily investigate whether TMT+NMES could improve physical function and pain compared with a passive control intervention. Methods We conducted a single-blind, randomized feasibility trial. Patients aged 60-85 years were allocated to TMT+NMES (n=31) or a passive control intervention (n=3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 57 publications
2
43
0
Order By: Relevance
“…Few studies in the current literature address lumbopelvic stability exercises associated with the use of NMES in core stability muscles. Six previous studies evaluated the effectiveness of NMES in the therapeutic approach of low back pain (11)(12)(13)(14)(15)(16)(17). As a conclusion of this study, the results showed significant effects for CNG compared to the other intervention groups.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Few studies in the current literature address lumbopelvic stability exercises associated with the use of NMES in core stability muscles. Six previous studies evaluated the effectiveness of NMES in the therapeutic approach of low back pain (11)(12)(13)(14)(15)(16)(17). As a conclusion of this study, the results showed significant effects for CNG compared to the other intervention groups.…”
Section: Discussionsupporting
confidence: 52%
“…It is important to note that high-intensity NMES used for muscle strengthening can be very uncomfortable for many patients (11). (17). All protocols, including that of this study, used the maximum visible and comfortable contraction to the patient as stimulation intensity.…”
Section: Discussionmentioning
confidence: 99%
“…This secondary analysis included baseline participant data from a sample of community-dwelling, cognitively intact (Folstein Mini-Mental State Exam score ≥ 24) older adults with CLBP who were enrolled in a randomized preliminary trial;[17] CLBP participants were compared to a sample of older adults without CLBP. For this study, older adults were defined using the range 60–85 years.…”
Section: Methodsmentioning
confidence: 99%
“…22 To be included, volunteers with LBP had to have a pain intensity of ≥3/10 for ≥3 months. Older adult volunteers, ages 60-85 years, without LBP were concurrently recruited through community centers and advertisements.…”
Section: Methodsmentioning
confidence: 99%